Democracy and resilient pro-social behavioral change: an experimental study - Kamei, Kenju (Social choice and welfare, 2016)
Both experimental and empirical studies have shown that democratically imposing a policy that encourages cooperation may increase its effectiveness by enhancing the voters' cooperation behavior. But, do those involved in the democratic decision-making process change their behavior when faced with an exogenously implemented rule? This paper experimentally shows that the voters that are involved in a successful democratic selection of a policy behave more pro-socially as consistent with recent studies. My experiment moreover shows that such a successful democratic imposition of the policy may increase the voters' level of cooperation even when the policy is undemocratically imposed.